1988
DOI: 10.1021/jo00259a001
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical cyclization of o-methylphenyl 1,3-diketones

Abstract: The photochemistry of five 1,3-dicarbonyl compounds, substituted at the 1-position with an o-methylphenyl group, has been investigated. Compounds 5a-c cyclize upon irradiation to give tetralones 6a and 6c and octahydroanthracene derivative 6b, respectively. Compounds 5d and 5e do not form similar photoproducts. Diketone 5c is the most efficient in this reaction, indicating that the reaction probably occurs via the keto tautomer. A mechanism involving initial y-hydrogen abstraction followed by interception of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…At this temperature the yield of the 3-hydroxyacrylate is significantly improved (entries 9,15,20,and 30,Table 4). In some cases, the only product isolated from the reaction was the desired 3-hydroxyacrylate, whereas 1 is ineffective as a catalyst at this temperature (entries 4 and 17, Table 4) due to slow dissociation of the THF ligand from 1.…”
Section: Resultsmentioning
confidence: 99%
“…At this temperature the yield of the 3-hydroxyacrylate is significantly improved (entries 9,15,20,and 30,Table 4). In some cases, the only product isolated from the reaction was the desired 3-hydroxyacrylate, whereas 1 is ineffective as a catalyst at this temperature (entries 4 and 17, Table 4) due to slow dissociation of the THF ligand from 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the 1 H-NMR spectrum of 1, a couple of broadened aromatic proton singlets at d 6.17 and 6.12, together with two pairs of mutually coupling one-proton doublets at d 3.06 (J = 16.9 Hz) and 2.94 (J = 16.9 Hz), and 2.71 (J = 17.1 Hz) and 2.88 (J = 17.1 Hz), suggested that it was a 3,4-dihydro-1-naphthalenone derivative carrying presumably a 3-hydroxy group. This assumption was substantiated by a set of carbon resonance lines in its 13 C-NMR spectrum at d 108.7 (CH), 163.9 (C), 101.6 (CH), 165.2 (C), 110.4 (C), 200.3 (C), 49.8 (CH 2 ), 72.5 (C), 41.8 (CH 2 ) and 143.7 (C) [7], [8]. Further reinforcement of the proposal was provided by extensive 2D NMR spectroscopic analyses (COSY, HMBC, HMQC and NO-SEY) allowing the exact assignment of all proton and carbon signals.…”
mentioning
confidence: 97%
“…Irradiation of Methyl 3-(2-Alkylphenyl)-2,2-dimethyl-3-oxopropanoates: Effect of Bulkiness of Ortho Alkyl Substituents on Photoreactivities. Irradiation of methyl 3- o -tolyl-2,2-dimethyl-3-oxopropanoate ( 4a ) in methanol with a high-pressure mercury lamp through a Pyrex filter gave the oxonaphthalenone 9a (23%) as the major product together with the benzocyclobutenol 10a (9%) at 94% conversion, in contrast to Hornback's report that naphthalenone derivatives were obtained exclusively in the photochemical reactions of o -tolyl 1,3-diketones in methanol . The yields of photoproducts 9 and 10 are given in Table .…”
Section: Resultsmentioning
confidence: 75%
“…Contrary to the extensively studied o -alkylphenyl ketones, the photochemistry of o -alkylphenyl 1,3-diketones is still less explored . Irradiation of some o -alkylphenyl 1,3-diketones in methanol gave naphthalenone derivatives exclusively instead of benzocyclobutenols . However, irradiation of o -alkylphenyl β-keto esters having no substituents on the alpha position did not afford any isolable photoproducts, though they produce dienols upon irradiation, as evidenced by deuterium incorporation …”
Section: Introductionmentioning
confidence: 96%